The minutes of a treaty held at Easton, in Pennsylvania, in October, 1758 : by the lieutenant governor of Pennsylvania, and the governor of New-Jersey ; with the chief sachems and warriors of the Mohawks, Oneydos, Onondagas, Cayugas, Senecas, Tuscaroras, Tuteloes, Nanticokes and Conoys, Chugnuts, Delawares, Unamies, Mohickons, Minisinks, and Wapings (Printed and sold by James Parker, printer to the government of New-Jersey, 1758)
In this treaty, agreements were made that the tribes would give up claims to lands in New Jersey but other lands in Pennsylvania were returned. Significantly, the tribes agreed to support the British against the French and the tribes would receive hunting ground lands on the western side of the Ohio River watershed and limit expansion of settlements west of the Allegheny Mountains after the end of the French-Indian War.